2017
DOI: 10.3390/en10122069
|View full text |Cite
|
Sign up to set email alerts
|

Integration Design and Optimization Control of a Dynamic Vibration Absorber for Electric Wheels with In-Wheel Motor

Abstract: This paper presents an integration design scheme and an optimization control strategy for electric wheels to suppress the in-wheel vibration and improve vehicle ride comfort. The in-wheel motor is considered as a dynamic vibration absorber (DVA), which is isolated from the unsprung mass by using a spring and a damper. The proposed DVA system is applicable for both the inner-rotor motor and outer-rotor motor. Parameters of the DVA system are optimized for the typical conditions, by using the particle swarm opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…In Figure 2, the tracking error ∆ω i is much larger than the compensation value β i , according to Equation (3), and e i is very large during the start-up of a multi-motor with load, thus making the amplitude-unlimited output of electromagnetic torque T ui much larger than the saturation value. However, the output of the speed loop controller generally contains a limiting part because of the system's safety requirements.…”
Section: Traditional Cross-coupling Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 2, the tracking error ∆ω i is much larger than the compensation value β i , according to Equation (3), and e i is very large during the start-up of a multi-motor with load, thus making the amplitude-unlimited output of electromagnetic torque T ui much larger than the saturation value. However, the output of the speed loop controller generally contains a limiting part because of the system's safety requirements.…”
Section: Traditional Cross-coupling Controlmentioning
confidence: 99%
“…With the development of modern industry, the synchronous control of multi-motors has been widely used in robotics, electric vehicles, steel rolling, papermaking, and other fields [1][2][3][4][5][6][7][8]. Shortening the start-up time and improving the synchronization performance of multi-motors are of both theoretical and practical significance for enhancing the control accuracy and stability of the system [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the impact of the vertical force of in-wheel motors greatly affected the vibration stability of the EV. Therefore, the isolation between the axle of the wheel and the bearing of the rotor had been added to reduce the EV's vibration and increase the EV's stability [3,7,8]. To further improve the ride comfort and stability of the EV, the vibration isolation of the in-wheel motor and EV's suspension system were then controlled [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…As the most popular means of traffic and transportation, automobile plays an increasingly important role in people's life and industrial production [1]. To a certain extent, Hybrid electric vehicle has injected new vitality into the automobile, and gradually become the century cleaner, efficient and convenient vehicle, and the driving motor system is the cornerstone to guarantee the performance of hybrid electric vehicle [2][3][4]. Excellent driving motor system is of great significance of the development of hybrid electric vehicles.…”
Section: Introductionmentioning
confidence: 99%